204k views
0 votes
How do I properly do this (in reference to the attached image)? I'm honestly not sure what it's asking me. Any help is much appreciated.

How do I properly do this (in reference to the attached image)? I'm honestly not sure-example-1

1 Answer

6 votes

Hello!

First of all, let's rewrite some square roots and their values:


\begin{gathered} √(1)=1 \\ √(4)=2 \\ √(9)=3 \\ √(16)=4 \\ √(25)=5 \\ √(36)=6 \end{gathered}

Knowing it, let's analyze your problem:

We know that the square root of 36 is 6.

Let's try to rewrite this expression but in another way, also obtaining the same result 6.

Let's do it:


\begin{gathered} √(4)\cdot√(9)=√(36) \\ 2\cdot3=6 \end{gathered}

Answer:


√(4)\cdot√(9)=√(36)

User Sjwdavies
by
4.8k points